Decrease of β-amyloid peptide precursor and ceruloplasmin mRNA levels in patients with Alzheimer’s disease support impairment of cellular iron efflux in this pathology - Silva, Bruno (2015)
This research was supported by the Fundação para a Ciência e a Tecnologia (FCT) [SFRH/BPD/29354/2006 to MM, SFRH/BD/60718/2009 to BS, and SFRH/BD/48671/2008 to LM]; Fundação Astrazeneca (Research Grant awarded through the “Programme of Support to Research”); Instituto Nacional de Saúde Dr. Ricardo Jorge; Portuguese Ministry of Health (Research Grant 53/2007 of the “Comissão de Fomento da Investigação em Cuidados de Saúde”); Lundbeck Portugal, Lda (Research Grant).